Catecholamine and Indolamine Pathway: A Case–Control Study in Fibromyalgia. Issue 5 (October 2018) - Rus, Alma; Molina, Francisco; Del Moral, María Luisa; Ramírez-Expósito, María Jesús; Martínez-Martos, José Manuel
Objectives: Fibromyalgia (FM) is a complex syndrome characterized by widespread pain. Its etiology is unclear, and diagnosis is difficult. The aim of this study was to assess plasma levels of monoamine neurotransmitters (catecholamines, indolamines, and intermediate metabolites) in patients with FM and healthy controls to investigate possible alterations in the metabolism of these molecules in FM. We also examined potential relationships between monoamine neurotransmitters and clinical features of FM. The predictive value of these molecules in FM was determined by receiver operating characteristic analysis. Method: We measured plasma catecholamines (epinephrine, norepinephrine, and dopamine), as well as indolamines and intermediary metabolites (serotonin or 5-hydroxytryptamine [5-HT], 5-hydroxyindolacetic acid [5-HIAA], 5-hydroxytryptophan [5-HTP], and N -acetyl-5-hydroxytryptamine [Nac-5-HT]) in 35 women with FM and 12 age-matched healthy women. Results: Higher levels of norepinephrine and lower levels of dopamine, 5-HT, 5-HIAA, and 5-HTP were found in women with FM in comparison with controls. Epinephrine and Nac-5-HT levels did not differ significantly between groups. Higher norepinephrine levels were associated with worse physical health status in FM patients. Also, plasma norepinephrine levels > 694.69 pg/ml might be an accurate predictor of FM. Conclusions: These findings show evidence of the dysregulation of the catecholamine and indolamine pathway in patients with FM, which may contribute to the physiopathology of this syndrome. In addition, the determination of plasma norepinephrine levels could help in the FM diagnosis.